2013
DOI: 10.1027/0227-5910/a000211
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Psychopathology and Suicidal Behavior In Schizophrenia

Abstract: The results indicate that clinicians should look for depression, anxiety, and guilt feelings, while positive and negative symptoms seem to be less relevant for suicide assessment in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…However, we noted previously with a larger sample (Pluck, Lekka, 2012), that neither severities of positive nor negative symptoms were linked to self-harm. A recent study of 509 schizophrenia patients has also reported that positive and negative symptoms are not predictive of suicide attempts (Jovanovic et al , 2013). Similarly, severity of positive and negative symptoms were not associated with any self-harm related brain activations in our study.…”
Section: Discussionsupporting
confidence: 37%
“…However, we noted previously with a larger sample (Pluck, Lekka, 2012), that neither severities of positive nor negative symptoms were linked to self-harm. A recent study of 509 schizophrenia patients has also reported that positive and negative symptoms are not predictive of suicide attempts (Jovanovic et al , 2013). Similarly, severity of positive and negative symptoms were not associated with any self-harm related brain activations in our study.…”
Section: Discussionsupporting
confidence: 37%
“…Identified correlates of SI in this population have included mood variability, negative symptoms, and depressive symptoms (Fialko et. al., 2006; Hocaoglu and Babuc, 2009; Jovanovic et al, 2013; Kontaxakis et al, 2004; Palmier-Claus et al, 2013), as well as positive symptoms (Taylor et al, 2010). We have previously examined the prevalence of SI in young people at clinical high-risk for psychosis (CHR), finding that 55% reported having suicidal thoughts (DeVylder et al, 2012), a prevalence replicated in other cohorts (Hutton et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While anxiety has been linked to suicide risk in schizophrenia (e.g., Hor and Taylor, 2010; Jovanovic et al, 2013; Lyu and Zhang, 2014), the effect is generally not as strong as the effect of depression. Our findings may be due to the smaller range on depressive symptoms in this sample, as one of the depression subscale items (i.e., suicide ideation) was removed prior to analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates were selected based on significant correlations with the outcome variable, as well as previous research establishing depression and anxiety as important risk factors for suicide ideation (e.g., Jovanovic et al, 2013; Yan et al, 2013). Because the BSI suicide ideation item evidenced substantial right skew, a Poisson regression was used (Coxe et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation